Wykonaj mnożenie i zredukuj wyrazy podobne.
a) ( 4a- 2)(2 -3a)=
b) ( x+2)(x2+ 2x- 4)=

c) (x+1)(x+2)(2x+3) =


Odpowiedź :

Odpowiedź:

( 4a- 2)(2 -3a)= - 12a2 + 14a - 4

( x+2)(2x+ 2x- 4)= 4x2 + 4x - 8

(x+1)(x+2)(2x+3) = 2x3 + 9x2 + 13x + 6

te 2 przy x to do kwadratu

Odpowiedź:

a) -12a²+14a-4

b) x³+4x²-8

c) 2x³+9x²+13x+6

Szczegółowe wyjaśnienie:

a) (4a-2)(2-3a) = 8a-12a²-4+6a = -12a²+14a-4

b) (x+2)(x²+2x-4) = x³+2x²-4x+2x²+4x-8 = x³+4x²-8

c) (x+1)(x+2)(2x+3) = (x+1)(2x²+3x+4x+6) = (x+1)(2x²+7x+6) = 2x³+7x²+6x+2x²+7x+6 = 2x³+9x²+13x+6